Potential role of nanotubes in context of clinical treatments? - Ranzinger, Julia; Rustom, Amin; Schwenger, Vedat (Communicative & integrative biology, 2013)
The recent awareness that eukaryotic cells can be linked and communicate via membranous nanotubes (NTs) has extended previous conceptions of cell-to-cell interaction. Apart from mediating functional connectivity between a broad range of cells, facilitating intercellular transmission of electric signals or various cellular components, there is strong evidence for participation of NTs in pathological processes of particular medical interest. In our recent study, we showed for the first time the existence of nanotubular connections between human primary peritoneal mesothelial cells (HPMCs) and provided insights to their actin/filopodia mediated building mechanism. Furthermore, we showed that tumor necrosis factor (TNF) significantly increased NT formation between HPMCs, pointing to a crucial role of NTs during inflammatory processes. Moreover, our study showed a strong correlation of NT occurrence and cellular cholesterol contents, demonstrating an interdependence of NT mediated cell communication, cytokine action and cholesterol homeostasis. Here, we further provide analysis on NT-formation processes.
Gesehen am 15.12.2021